Qualitative comparison between carrier-based and classical tissue microarrays - Kriegsmann, Katharina; Leichsenring, Jonas; Zgorzelski, Christiane; Longuespée, Rémi; Harms, Alexander; Kazdal, Daniel; Stenzinger, Albrecht; Warth, Arne; Kriegsmann, Mark (Applied immunohistochemistry & molecular morphology, 2017)
Tissue microarrays (TMAs) are commonly used in biomarker research. To enhance the efficacy of TMAs and to avoid floating or folding of tissue cores, various improvements such as the application of carriers and melting techniques have been proposed. Compared with classical TMAs (cTMAs), carrier-based TMAs (cbTMAs) have been shown to have several advantages including sample handling and sectioning. Up to now, little is known about the efficacy and quality of cbTMAs compared with cTMAs. Thus, we set out to compare both types systematically. We constructed 5 spleen-based TMAs and 5 cTMAs with 10×10 different tissue types each. The total number of available cores, the number of folded cores, and the total core area was measured and evaluated by digital pathology. About 2% of cores got lost due to floating in both, cbTMAs and cTMAs, respectively. The remaining cores showed significant differences with regard to core integrity as about 1% of cbTMA cores and 9% of cTMA cores were folded (P<0.01). Folding or rolling was associated with specific tissue types. The size of the cores was smaller and less variable in cbTMAs (0.86±0.06 mm2) compared with cTMAs (0.97±0.14 mm2). The application of cbTMAs is an easy, inexpensive, and effective way to improve TMA-based research....